HOAX TEXT STRUCTURE ON SOCIAL MEDIA - A. Yusdianti Tenriawali; Saidna Zulfiqar Bin Tahir; Mansyur Nawawi; Belinda Sam; Hamiru Hamiru; Muhamad Chairul Basrun Umanailo; La Eko Lapandewa (Media Bina Ilmiah, 2023)
This study aims to analyze the text of the online hoax news 'Consumption of Yellow Pumpkin Brings Benefits to Cure Covid-19' on Indonesian social media. The analysis in this study consists of an analysis of the form and meaning of texts that are believed to contain hoax information. In addition, this research also contains information about the impact that hoaxes can have. The research method used is descriptive qualitative, which is critical, with data collection techniques in the form of documentation techniques, notes, and literature study. This study's data are news texts believed to contain false information. Data analysis techniques in this study consisted of data identification, classification, data analysis, and the conclusion of data analysis results. The study results show that the text's structure consists of contrast discourse strategies, exaggeration, and enumeration and climaxes with linguistic markers in the form of words and sentences. The meaning found is to influence and convince the reader. Apart from that, the online news texts analyzed also show the characteristics of hoax texts because there are unclear characteristics of news sources, and there are suggestions for disseminating this information. Based on the literature study, information was also found that until now, there has been no research on specific foods that can help cure Covid-19. Therefore it can be concluded the information in the news text 'Consumption of Yellow Pumpkin Brings Benefits to Cure Covid-19', which is analyzed, contains hoax information.